Evaluation of orange peel (Citrus sinensis) bioplastic through morphological and thermo-mechanical characteristics (Agro Productividad, 2024)
Objective: To evaluate the morphological and thermo-mechanical properties of a biofilm obtained from orange peel.Design/methodology/approach: Pectin, a polysaccharide obtained from orange peel, has the potential to be used as a raw material in the bioplastics industry. The samples obtained were characterized by the Scanning Electron Microscopy (SEM) technique, mechanical tension and by thermogravimetric analysis (TGA).Results: The elastic modulus was in the range of 7.7 to 29.9 MPa, depending on the plasticizer content. The thermogravimetric analysis showed a thermal decomposition between 134.42 to 153.98 °C depending on the plasticizer content and up to five events were identified.Limitations of the study/implications: During the process, a pectin yield of 75% of orange peel was obtained.Findings/conclusions: In developing countries such as Mexico, waste originating from agricultural and agro-industrial activities represents an important source of natural carbohydrate polymers that can be used to produce bioplastics, intended to replace petroleum-derived materials. In the case of orange peel, it can become a potential raw material to obtain value-added products in sectors of the food industry. These results indicated that our pectin has suitable properties to be used as raw material for the manufacture of bioplastics